Do manufacturing plants respond to exogenous changes in electricity prices? Evidence from administrative micro-data - Kathrine von Graevenitz; Elisa Rottner (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2022)
Climate policy often implies increasing energy prices. Due to incomplete regulation across the globe, concerns about their competitiveness and employment effects play an important role in the policy debate. Using micro-data on electricity network charges and the official census data for Germany, we study the impact of rising electricity costs on plant performance in German Manufacturing. Electricity network charges are determined through regulation in Germany and therefore exogenous to manufacturing plants, while making up a substantial share of final electricity prices. Our estimates imply a negative own-price elasticity of electricity of -0.4 to -0.6 in the short-run: A one cent increase in average network charges leads to a decrease in electricity procurement of roughly 3 %. There is suggestive evidence that this elasticity of response is decreasing over time, in line with nonlinearly increasing marginal abatement costs. Generally, we do not find significant effects on revenues, investments or capital stocks.
Keywords: D22; L60; Q41; Q48; 330; Network charges; Electricity Use; Firm Performance; Climate Policy; Manufacturing